Out from underdevelopment revisited - Mittelman, James H. (London, 1997)
Development may be best understood in terms of the interplay among capital accumulation, the state, and class. Subject to globalizing structures, classes, in turn, are examined in light of their interactions with culture, especially gender and religion as well as ecology. Case-studies - Brazil, the Asian newly industrializing countries, China, and Mozambique - reveal three possibilities for overcoming underdevelopment: joining, leaving, or weaving through global capitalism. The conclusions do not fail to present specific principles upon which policies can be based.
Keywords: International economic relations